Analysis of Students' Metacognition Skills in Problem Solving on Thermochemical Materials - Manaa, Ramayanti N; Lukum, Astin; Tangio, Julhim S; Pikoli, Masrid; Alio, La; Sihaloho, Mangara; Sangkota, Vivi Dia Afrianti (Universitas Negeri Gorontalo, 2025)
This research is a descriptive qualitative research that aims to determine students' metacognition skills in problem solving on thermochemical material. The instrument used in this research is a 5-number description test in problem solving questions to measure students' metacognition skills. The subjects in this study were 34 students of class XI SMA Negeri 1 Tapa. The data analysis technique in this research is descriptive qualitative analysis which includes the stages of data reduction, data presentation, data analysis and conclusion drawing. The results showed that from the indicators of the questions given, students get an average value of the ability of metacognition skills for each indicator, namely: planning indicators by 67.8%, monitoring indicators by 48.2%, and evaluation indicators by 21.2%. The average results obtained on all indicators can be concluded that the ability of students' metacognitive skills on planning indicators is quite high, monitoring indicators are moderate, and evaluation indicators are low.